A review of FDA approved drugs and their formulations for the treatment of breast cancer - Chaurasia, Mohini; Singh, Romi; Sur, Srija; Flora, S. J. S. (Frontiers in Pharmacology, 2023)
Breast cancer is one of the most diagnosed solid cancers globally. Extensive research has been going on for decades to meet the challenges of treating solid tumors with selective compounds. This article aims to summarize the therapeutic agents which are either being used or are currently under approval for use in the treatment or mitigation of breast cancer by the US FDA, to date.A structured search of bibliographic databases for previously published peer-reviewed research papers on registered molecules was explored and data was sorted in terms of various categories of drugs used in first line/adjuvant therapy for different stages of breast cancer. We included more than 300 peer-reviewed papers, including both research and reviews articles, in order to provide readers an useful comprehensive information. A list of 39 drugs are discussed along with their current status, dose protocols, mechanism of action, pharmacokinetics, possible side effects, and marketed formulations. Another interesting aspect of the article included focusing on novel formulations of these drugs which are currently in clinical trials or in the process of approval. This exhaustive review thus shall be a one-stop solution for researchers who are working in the areas of formulation development for these drugs.